Comparative Study of Indonesian Education System with Malaysia in Legal Form Approach - Fauzi, Muhammad Muzaki; Juniarta, Gladys Intan; Fajar, Ikhsan Muhammad; Zikri, Iqmal Maulana; Yuningsih, Neneng Yani (Peneliti.net, 2025)
Education plays an important role as the foundation of national development which is regulated by law. This research aims to examine the comparison of legal frameworks and education policies in Indonesia and Malaysia by focusing on the legal-formal approach. The method used is library research with a qualitative descriptive approach. Data were obtained through a search of the constitution, education laws, ministerial regulations, and national education policy documents from each country. The results show that Indonesia applies a decentralized system by giving great authority to local governments, which allows the integration of local values but also faces challenges of consistency and quality. Malaysia, with its centralized system under the Ministry of Education, allows for a more equitable standardization of education to remote areas. Based on Dr. Nazily's (2020) theory, the effectiveness of education policy is largely determined by strict legal norms, systematic implementation tools and continuous evaluation mechanisms. This analysis shows that Indonesia excels in flexibility and cultural relevance, while Malaysia excels in implementation efficiency and monitoring. This study is expected to provide solutions to improve the quality and equity of national education through learning from both systems.